Multicointegration analysis on the high yielding Boro rice of six selected districts in Bangladesh - Karmokar, Provash Kumar; Shitan, Mahendran; Beg, A. B. M. Rabiul Alam (Academic Journals, 2011)
Rice is the principal agricultural crop in Bangladesh and Boro rice is a special variety of rice. Production of Boro rice differs from district to district due to various factors like environment, geographical location, climatic changes, etc. In this article, our particular interest is whether or not cointegration/multicointegration exists amongst six major rice producing districts in Bangladesh. The six districts are Rajshahi, Dinajpur, Tangail, Kushtia, Mymensingh and Barisal. Multicointegration of rice productions in these districts is analyzed within the error correction framework. Our analysis indicated that multicointegtation exist amongst Boro rice production of Mymensingh, Boro rice production of Barisal and the estimated Boro rice production of Kushtia. As such, the error correction technique was required and the results indicated that the estimated speed of adjustment coefficient of the ‘error correction model’ for Barisal indicates that approximately 66% of any deviation from the long-run path is corrected within a year. Further, the Granger causality from Mymensingh and estimated Boro production of Kushtia to Barisal exist within this estimated ‘error correction model’. The results of this study would aid in policy decision making.